Enhancing Small Industrial Enterprise Performance: The Influence of Entrepreneurial Competence, Education, and Self-Efficacy - Saidun Hutasuhut; Reza Aditia; Thamrin Thamrin; Syamsuyurnita Syamsuyurnita (AL-ISHLAH: Jurnal Pendidikan, 2024)
This quantitative study examines the impact of entrepreneurial competence and education on the performance of small industrial enterprises, specifically in Medan's leather shoes and wood furniture industries. The research focuses on a sample of 154 businesses from a total population of 250, utilizing questionnaires and Structural Equation Modeling-Partial Least Squares (SEM-PLS) for analysis. The findings highlight the positive influence of entrepreneurial competence and non-formal education on business performance. The study underscores self-efficacy's role as a mediator between entrepreneurial competence and performance, indicating that entrepreneurs with higher self-efficacy effectively navigate business challenges. However, the study doesn't confirm self-efficacy as a mediator for formal and non-formal education's impact on performance. This suggests that while competence and non-formal education directly benefit performance, the interplay of self-efficacy with formal education is more complex. In conclusion, the research emphasizes the importance of entrepreneurial competence for business success and the role of self-efficacy in overcoming challenges. While self-efficacy's role in formal education needs more exploration, this study enhances understanding of factors affecting small industrial enterprises' performance, offering practical insights for ambitious entrepreneurs.